Engineering materials properties and selection - Budinski, Kenneth G.; Budinski, Michael K. (Pearson/Prentice Hall, 2005)
Co-authored by Kenneth G. Budinski and Michael K. Budinski, his son, with over 50 years of combined industry experience in the field, this practical, understandable introduction to engineering materials theory and industry-standard selection practices provides readers with the working knowledge to (1) make an informed selection of materials for engineering applications and (2) correctly specify materials on drawings and purchasing documents. Encompassing all significant material systems--metals, ceramics, plastics, and composites--this text incorporates the most up-to-date information on material usage and availability, addresses the increasingly global nature of the field, and reflects the suggestions of numerous adopters of previous editions. Within the four major material categories, this edition includes specific coverage of international metal buying, plastic families, AsurvivorA ceramics, and composite coatings. Other topics include surface engineering; tribology (friction, wear and lubrication); material properties; cemented carbides; steel making; heat treating; and corrosion--including a treatment of electrochemistry. Appropriate for all materials engineers.